Evaluation of potential sustainable bedding substrates focusing on preference, behavior, and stress physiology in rats: a pilot study - Vogt, Miriam A.; Geiger, Lisa Marie Joy; Härtel, Talia; Follert, Philipp; Palme, Rupert; Chourbaji, Sabine (Animals, 2021)
Ensuring optimal housing conditions for laboratory animals is a crucial prerequisite for high-quality and ethically justifiable in vivo science. In addition to guaranteeing animal welfare and promoting scientific validity, environmental sustainability is also increasingly gaining attention in laboratory animal facilities. Consequently, comprehensive management of such aspects is one of the core tasks of any research vivarium. Hygienic monitoring and adhering to standardized experimental protocols have been highlighted in the past; nevertheless, various environmental aspects of housing animals still need to be evaluated in greater depth. In this pilot study, we aimed at assessing the suitability of spelt and corncob as economical and ecologically friendly bedding substrates as compared with commonly used aspen wood chips. Therefore, following a descriptive study design, we examined the preferences of male and female Wistar rats for corncob and spelt under specific conditions. In addition, we evaluated potential effects on behavior, metabolism, and stress physiology. The type of bedding did not seem to influence behavior in the observed parameters but did have time- and sex-dependent effects on blood glucose. Furthermore, housing animals on spelt led to a significant reduction in food consumption, probably compensated for by the intake of spelt, and although it did not influence glucose levels, it may have certainly impacted the nutrient supply. Our descriptive pilot study, therefore, highlights the importance of a thorough condition-associated evaluation of even seemingly marginal environmental factors, when balancing potential cost-benefit advances in sustainability and questions of standardization and reproducibility of experimental protocols.